Strategi Seni Pertunjukan Dengan Segmentasi Pariwisata (Kajian Pertunjukan Tallu Cappa’ Di Wisata Pulau Camba-Cambang Pangkep) - Damar Tri Afrianto; Muhajir (Politeknik Pariwisata Makassar, Indonesia, 2020)
Art and tourism rarely become concerned in a study or research. Though it is allegedly both have the power of mutual influence and profitable. Efforts have been made to make the art as a medium to develop the world of tourism but sometimes have no strategy and formulation appropriately so that the art is just a patch or entertainment when melalkukan travel. Through the study and analysis of Tallu Cappa's performances by Makassar artists Muhajir can be formulated conceptual strategy or some strategic thinking related to performing arts and tourism. Among others, 1) presentation of Multi-disciplinary Art and Innovative Packaging, 2) Collaboration of art with the concept of tourism and 3) Excavation of local Wisdom as an effort to get the aesthetic experience for tourists. Performing works of artists Muhajir perceived successfully menyjiakan concept performances with tourism segmentation. So hopefully this strategy becomes the initial basis for the development of art as an effective, innovative and cultured tourism promotion media.